The newborn screening tests in Brazil: regional and socioeconomic prevalence and inequalities in 2013 and 2019 - Letícia R. Dias; Yaná T. Tomasi; Antonio F. Boing (Elsevier, 2024)
Objective: To analyze the prevalence evolution of Guthrie, hearing, and eye screening testing among newborns in Brazil, between 2013 and 2019, according to demographic and socioeconomic characteristics. Methods: This is a cross-sectional study with data from 5231 infants from the Pesquisa Nacional de Saúde (PNS), in 2013, and 6637 infants, in 2019, for the Guthrie test, hearing, and red reflex tests. The authors analyzed the outcomes according to the region of residence, self-reported color/race, having health insurance, and per capita household income. By using bivariate and multivariate Poisson regression models, the prevalence ratios and their respective 95 % Confidence Intervals (CI95%) were calculated for each year. Results: In 2013, Guthrie test, hearing, and red reflex tests were performed in 96.5 % (95%CI 95,8;97,0), 65.8 % (95%CI 63,9;67,7), and 60.4 % (95%CI 58,5;62,3) of infants, respectively. In 2019, the prevalence was 97.8 % (95%CI 97,3;98,2) in the Guthrie test, 81.6 % (95%CI 80,3;82,9) in the hearing test, and 78.6 % (95%CI 77,1;79,9) in the red reflex test. The testing frequency was higher among residents of the Southeast and South regions of Brazil, among infants whose mother or guardian was white, had health insurance, and was in the higher income strata; and the most evident differences were in the eye and hearing testing. Conclusions: The coverage inequalities according to the region of residence, income, and having health insurance highlight the need to use strategies that enable exams to be carried out, with more information about their importance, encompassing actions from primary care, prenatal care to the puerperium, aiming at universal access and equity.